2007
DOI: 10.1016/j.neuropharm.2006.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Antinociception mediated by α2-adrenergic activation involves increasing tumor necrosis factor α (TNFα) expression and restoring TNFα and α2-adrenergic inhibition of norepinephrine release

Abstract: The central component that establishes chronic pain from peripheral nerve injury is associated with increased tumor necrosis factor-α (TNFα) production in the brain. This study examined TNFα and its reciprocally permissive role with α 2 -adrenergic activation during peak and progressive decline of thermal hyperalgesia in sciatic nerve chronic constriction injury (CCI). Accumulation of TNFα mRNA (in situ hybridization) increases in the hippocampus and locus coeruleus during the onset of neuropathic pain and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
(120 reference statements)
4
18
0
Order By: Relevance
“…The decrease in pain is associated with a full switch in ␣ 2 -adrenergic and TNF␣ regulation of NE release from inhibition to potentiation of NE release from adrenergic neurons in the hippocampus. This switch or reversal of function counteracts the decrease in NE release that occurs during the development of hyperalgesia (Covey et al, 2000;Ignatowski et al, 2005;Spengler et al, 2007).…”
Section: Reciprocal Interactions Between Tnf˛ and The ˛2-ar In Pain Amentioning
confidence: 97%
See 3 more Smart Citations
“…The decrease in pain is associated with a full switch in ␣ 2 -adrenergic and TNF␣ regulation of NE release from inhibition to potentiation of NE release from adrenergic neurons in the hippocampus. This switch or reversal of function counteracts the decrease in NE release that occurs during the development of hyperalgesia (Covey et al, 2000;Ignatowski et al, 2005;Spengler et al, 2007).…”
Section: Reciprocal Interactions Between Tnf˛ and The ˛2-ar In Pain Amentioning
confidence: 97%
“…(a) Initially (acute), upon dosing, some antidepressants indirectly decrease TNF through blockade of monoamine reuptake or monoamine oxidase inhibition. This blockade increases NE availability allowing for ␣2-AR activation (it is coupled to G␣ i/o protein); the ␣2-AR-G␣ i/o configuration supports a decrease in TNF (see 'd' above) (Ignatowski et al, 1996a;Nickola et al, 2000;Renauld and Spengler, 2002;Reynolds et al, 2005a;Spengler et al, 2007). Also, tricyclic antidepressants, atypical antidepressants (bupropion, rolipram), and electroconvulsive therapy directly reduce TNF levels in the brain (Brustolim et al, 2006;Buttini et al, 1997;Hestad et al, 2003;Ignatowski et al, 1996b;Ignatowski and Spengler, 1994;Nickola et al, 2001).…”
Section: Reciprocal Interactions Between Tnf˛ and The ˛2-ar In Pain Amentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that stress-produced hormones (such as noradrenaline) in the blood serum served as indirect criteria of the functional activity of the endogenic antinociceptive structures before and after the treatment 4 only T clonidine (CloG) did not show any decrease in plasma noradrenaline levels. Although α2-adrenergic receptor activation with clonidine in rats experiencing hyperalgesia inhibited noradrenaline release 13 , and clonidine resulted in dose-dependent noradrenaline decrease 14 , by 6-h evaluation the dose used resulted in no evident decrease of noradrenaline by itself. However, the same dose further enhanced nordrenaline decrease after T fentanyl at 3-h evaluation.…”
Section: Discussionmentioning
confidence: 89%